ISOLATION AND IDENTIFICATION OF CELLULOLYTIC BACTERIA FROM WASTE ORGANIC VEGETABLES AND FRUITS FOR ROLE IN MAKING MATERIALS BIOGAS. - Ateng Supriyatna; Ida Rohimah; Yani Suryani; Sumiyati Sa’adah (JURNAL ISTEK, 2012)
Research onisolationandidentification ofcellulolyticbacteriafromwasteorganicvegetablesand fruitsas ingredientsthat play a rolein the manufacture ofbiogashas been carried out. Bacteria isolates were obtained from wastevegetableand fruitsfromthe marketGedebageBandung. The aim of research is to know diversity of bacteria that growandcellulolyticbacterialisolateswhatever ison thewastevegetablesand fruitsthat play a rolein makingbiogas. Media that used for cultivation and isolation bacteria is NA (Natrium Agar). Bacteria isolation is conducted by using serial dilution, pour plate and streak plate methods. The determinecellulolyticbacteriausedselective mediaSA(Cellulose Agar) andidentification ofbacteriacarriedto genus levelbased onmorphologicalandbiochemicalcharacterizationthat refersto theguidelinesof identificationof bacteria (Bergey's Manual ofDeterminativeBacteriologyin 1994). In this research, we successfully isolated 13 isolates bacteria that consist of 10 genera. Identification result indicates that isolate B1, B8, B9, and B12 are Bacillus; isolate B2 is Cellulomonas, isolate B4 is Microbacterium, isolate B5 is Neisseria, isolate B6 is Streptococcus and isolate B7 is Strepmycetes. Test cellulose indicates that the cellulolyticbacteriaareBacillus, Cellulomonas, Microbacterium, Streptomycetes, Streptococcus, andNeisseria. Based ontestinHCdegradation ofcellulosein the mediaSA, Streptomycetesis bacteria thathave thehighestHCratioandthelowestin thegenusNeisseria. The bacteriawere chosen becausethe bacteriahave ahighability tohydrolyzecelluloseinso-called cellulolyticbacteriaand potentiallyin the manufacture ofbiogas.